Shetland. Season five [videorecording (DVD)] - Henshall, Douglas, 1965-; O'Donnell, Alison; Robertson, Steven; Cleeves, Ann (BBC Worldwide Ltd. : ITV Studios Limited, 2019)
Follows DI Jimmy Perez and his team as their investigation of a young Nigerian man's murder leads them to human trafficking network spanning Scotland's rural communities.